Violent peace: community relations in the Chittagong Hill Tracts (CHT) in Bangladesh after the Peace Accord. Issue 3 (4th May 2022) - Islam, Rafiqul; Schech, Susanne; Saikia, Udoy
ABSTRACT: The 1997 Peace Accord in the Chittagong Hill Tracts (CHT) promised to bring an end to decades of violence in the region. However, 25 years later, the region is still experiencing social conflict between indigenous Pahari people and Bengalis, who have migrated and settled in large numbers since the 1970s. This paper examines the reasons for the continuation of social conflict through a survey on community attitudes and relations. The survey findings show that the legacy of migration and conflict in the CHT is still evident in starkly different views on resources, conflict, and community relations. These findings support the argument that the migration of people with different ethnic backgrounds into regions inhabited by ethnic minorities causes competition for resources that may generate conflict and violence with long-lasting consequences.